Demokrasi, Kekuatan Politik dan Ukuran Pemerintah Daerah Terhadap Transparansi Pemerintah Daerah Provinsi di Indonesia - Sindy Putri Nur Rahmadanni; Deviani Deviani (Jurnal Akademi Akuntansi, 2024)
Purpose: The study aims to examine and analyze the effect of democracy, political strength and local government size on transparency of provincial local government in Indonesia. Methodology/Approach: The study used quantitative methods. The secondary data was collected from provincial local government in Indonesia from 2018 to 2020. Transparency of ptovincial was measured using the result of monitoring and evaluation of public information from the Commission of Information for Indonesia (Komisi Informasi Indonesia). Findings: The study finds that democracy and local government size had a positive effect on transparency of provincial local government in Indonesia and the political strength has no effect on transparency of provincial local government in Indonesia. Practical and Theoritical Contribution/Originality: This study contributes to add insight and knowledge in the field of accounting, especially in public sector accounting about the factors that influence transparency in the local government.